The System Framework for Profiling the Content of Web Portals - Weichbroth, Paweł (Architektura systemu profilowania treści witryn internetowych, 2010)
This paper presents a novel approach to profiling the content of Web portals based on discovered association rules from www servers' log files. For this purpose there has been elaborated the agent architecture which is supported by data base and world wide web servers, After a short foreword, in general extent, a description of the system's components is given, next, the logging process of users' requests to files hosted by the www server is outlined in detail. Then, the functionality of preprocessing, reasoning, dynamic links and the manager agents is characterized. The whole work is finished by conclusions and remarks on future work, in which selected implementation aspects of presented system are pointed out.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 104, s. 186-193
Keywords: association rules; Web server; agent framework